Mitochondrial DNA Damage and Animal Longevity: Insights from Comparative Studies - Reinald Pamplona (Journal of Aging Research)
Chemical reactions in living cells are under strict enzyme control and conform to a tightly regulated metabolic program. However, uncontrolled and potentially deleterious endogenous reactions occur, even under physiological conditions. Aging, in this chemical context, could be viewed as an entropic process, the result of chemical side reactions that chronically and cumulatively degrade the function of biological systems. Mitochondria are a main source of reactive oxygen species (ROS) and chemical sidereactions in healthy aerobic tissues and are the only known extranuclear cellular organelles in animal cells that contain their own DNA (mtDNA). ROS can modify mtDNA directly at the sugar-phosphate backbone or at the bases, producing many different oxidatively modified purines and pyrimidines, as well as single and double strand breaks and DNA mutations. In this scenario, natural selection tends to decrease the mitochondrial ROS generation, the oxidative damage to mtDNA, and the mitochondrial mutation rate in long-lived species, in agreement with the mitochondrial oxidative stress theory of aging.